Cross method and design process for DSF elements - Ilter, Sertaç; Vural, Müjdem M. (Open House International Association, 2017)
The double-skin façade (DSF) is one of the most crucial paradigms of building envelope design in last decades. DSF prospects a unified architectural phenomenon based on comfort rank of building driven by the dogmas of aestheticglass façade and practical- natural ventilation aspirations. Therefore, the utilization of DSF has been the most prevalent catalyst for architectural design. The study discusses to structure a valid evaluation method focusing on DSF elements in order to fragment human comfort standards within asserting an accurate system in the preliminary design stage. The study significantly examines the tools/ways of integrating DSFs' human comfort parameters in contemporary architecture though a convincing design system. Apparently, the study aims to provide a proposed guideline within a established analyzing system for architects in order to better formation of DSF elements; which refers and promote the human comfort standards. The results demonstrate a modest insight on understanding the potentials of DSF elements in the early design stage significantly following defined architectural conceptions; cooling, lighting, thermal, acoustic and visual comfort intensity. Based on obtained data; study aims to enclose a diminutive knowledge or demonstration of how the concept might work for future development of contemporary architecture within DSF area.
Keywords: Cross method; Design process; Double skin façade; Double skin façade elements; Energy performance